Analysis of Glimepiride in Human Blood and Urine by Thin Layer Chromatography and UV Spectrophotometry - Ibragimova, Mareta Mukharbekovna; Ikramov, Latif Tulaganovich (The Bulletin of Legal Medicine, 2015)
Objective: An increasing numbers of cases of poisonings by glimepiride, either attempted suicide or accidental, combined with the absence of reliable methods for the detection and quantitation of glimepiride in biological matrices is the basis for the need for the development of new analytical techniques for forensic analysis.Materials and Methods: Analyses were performed using drug- free biological fluids (whole blood and urine). Specimens were spiked with chromatographically pure glimepiride. After hydrolysis with diluted hydrochloric acid at 50-60 °C for 15-20 min and a double extraction into chloroform, glimepiride was identified by thin-layer chromatography. Standard solution of glimepiride (1 mg/mL) and Sorbfil chromatographic plates were used for thin-layer chromatography. The thin-layer chromatography studies showed that the best mobile phase was chloroform:acetone (9:1), Rf value of glimepiride in five examinations was 0.37±0.02. Visualization of glimepiride was achieved byspraying with Dragendorff’s, Bushard’s, or diphenylcarbazone-chloroform solution followed by mercuric sulphate. The limit of detection of pure glimepiride by thin-layer chromatography was 0.5 p/mL, 1.5 p g/mL in whole blood and 1.0 p g/mL in urine. For spectrophotometric determinations of glimepiride, a UV/VIS spectrophotometer with 1 cm matches quartz cell was used. Standard solutions of glimepiride in ethanol were prepared at concentrations of 1-50 p g/mL and scanned in full-scan mode between 200-400 nm.Results and Conclusion: The wavelength maxima for glimepiride was found to be 227 nm with molar absorptivity of 3.2685x10 4 l/mol/cm. Beer’s law was obeyed in the concentration range of 2-40 p g/mL. The limit of detection and limit of quantification were found to be 0.97 p g/mL and 2.70 p g/mL, respectively. The results have been successfully applied in blood of patients after oral administration and on postmortem blood in an overdose death.Keywords: Glimepiride, Thin-layer chromatography, Spectrophotometry.
Keywords: glimepiride; thin-layer chromatography; spectrophotometry